Premature Constriction of Fetal Ductus Arteriosus Caused by Sertraline in a Pregnant Woman: A Case Report - Alireza Golbabaei; Elham sadat Alavi moghaddam; Hooman Mohammad Talebi (Clinical Case Reports)
ABSTRACT Fetal ductus arteriosus was treated in a 39‐year‐old pregnant woman in the 33rd week After psychiatric consultation and discontinuation of sertraline which underscores the association of sertraline with premature ductus arteriosus constriction.